Resposta hidrológica de uma grande bacia hidrográfica no semiárido brasileiro diante de cenários de transposição hídrica e racionalização do uso de reservatórios não estratégicos - Lima, Thales Bruno Rodrigues (2020)
The water scarcity has affected an increasing number of people around the world, with communities in the arid and semi-arid regions being the most affected. In the Brazilian semi-arid, the construction of dams was the main strategy to improve the water availability of the region, culminating with the establishment of a dense reservoir network where smalls and big reservoirs play complementary tasks at the water arrangement established. In view of the increasing demands and recurrent droughts in the region, other water structures such as wells, cisterns and recently water transfer channels have been directed to the hydrographic basins of Northern Northeastern to overcome the local water deficit. From a water management perspective, the present work sought to analyze the hydrologic response of Jaguaribe River Basin by studying the volume stored in strategic reservoirs (Arneiroz II, Banabuiú, Benguê, Canoas, Castanhão, Cedro, Fogareiro, Orós, Pedras Brancas, Quixeramobim, Riacho do Sangue e Trussu) considering the following scenarios: intense water use from small reservoirs and transposition of the São Francisco River to the Castanhão reservoir. Initially, in the calibration/validation of the WASA model, its sensitivity to the hydraulic conductivity of the crystalline basement and saturated hydraulic conductivity of the soil was evidenced. The WASA model satisfactorily simulated (NSE > 0.5) the volume stored in 4 (Cedro, Orós, Pedras Brancas and Trussu reservoirs) of 12 analyzed reservoirs. In the others, it reproduced the dynamic of filling and emptying the reservoirs. The first scenario evaluated points out that the intense use of water from small reservoirs does not compromise the volume accumulated in strategic reservoirs. In the transposition scenario (2002 – 2011), it was verified that the water transfer would reduce by 247, 51, 32 and 1 day the period in which the volume of the Castanhão reservoir would be below 15%, 20%, 25% and 30%, respectively. Thus, the intense water use from small dams and the transposition are strategies that can be used simultaneously to meet different demands, aiming to ensure water security in the region.